EVALUATION OF ANTI PCL-1 ANTIBODY TITER IN A GROUP OF HEALTHY SCHOOL CHILDREN WHO LIVE IN LEPROSY ENDEMIC AREA FROM 2007–2010 - putri, rachmah diana; amiruddin, M. dali; tabri, farida; Adriaty, Dinar; Wahyuni, ratna; iswahyudi, iswahyudi; agusni, indropo; izumi, shinzo (Indonesian Journal of Tropical and Infectious Disease, 2010)
The "Iceberg phenomene” has been used to explain this situation which indicate that these new leprosy cases is originated from Subclinical Leprosy. Fifty eight healthy school children who live in Jeneponto Regency, a leprosy endemic area in South Sulawesi were recruited. The first examination was performed in 2007 and sera samples were kept in deep freeze refrigerator. In 2010 these children were re-examined for clinical leprosy and sera were collected again. ELISA study was performed simultaneously to these 58 pairs of sera (2007 & 2010) for measuring the titer of IgM anti PGL-1 antibody (ELISA) and the level 605u/ml was regarded as cut off value. After three years evaluation, none of these children showed any clinical signs of leprosy, but 20 of 22 ( 90.9%) children were remained sero-positive and only 2 (9.1%) became sero-negatives. In other sites, 5 children that previously sero-negatives became sero-positives after 3 years. Eight of 10 (80%) children who showed sero (+) with high titer (>1.000u/ml) in 2007, were also remained in high titer. The mean titer of 2007 was 627.8 u/ml, and after3 years became 723.9 u/ml (p<0.05). Although there is no progression from Subclinical to Manifest Leprosy cases among these children, the number of sero (+) cases were increased and the mean titer of IgM anti PGL-1 antibody was significantly increased.. The majority who previously showed high anti PGL-1 antibody titer, remained in high level. This study support the "iceberg phenomene” theory in Leprosy.